THE DEVELOPMENT OF E-LEARNING MODULE BASED ON PROJECT-BASED LEARNING (PJBL) FOR ELECTRIC MOTOR INSTALLATION COURSE - Rusmanto, Rusmanto; Rukun, Kasman (Journal of Education Research and Evaluation, 2020)
The purpose of this research was to develop an E-learning module that can help students learn independently and valid, practical, and effective. This study was the Research and Development (R&D) research method with the 4D (four-D) development model. The research phase includes define (the defining stage), design (the design phase), develop (the development stage), and disseminate (the deployment stage). The instrument used in this study was a questionnaire used to measure validity and practicality. Meanwhile, to measure the effectiveness, it was using the test instrument in the form of multiple-choice questions. E-learning module was based on Project Based Learning. The results showed that the E-learning module was declared valid with a validity score was 91.50 based on the validation of three media validators and in terms of the validity of the material declared valid with the score was 91.50 from three teachers. E-learning modules stated to be very practical based on teacher and student responses. This showed that the E-learning module effectively used as one of the teaching materials in learning in improving student learning outcomes. Based on the findings of the study it can be recommended that the E-learning module was an alternative teaching material in learning that can be used in learning on electric motorization (IML) subjects.